Pendekatan Majaz Dalam Penafsiran Al-Qur’an - Syarifah, Nurus (Al Irsyad: Jurnal Studi Islam, 2022)
The Qur’an is the holy book of Muslims that was revealed using Arabic, which is very clear and clear. To understand the Qur’an well, of course one must master the Arabic language well. Without it the Qur’an would not be able to be understood. The Qur’an which is summarized in it about monotheism, shari'ah, morals, and so on has various ways of conveying meaning called the Qur’anic language style, one of which is majaz. The existence of the majaz approach in conveying meaning through the interpretation of the Qur’an has various types, stages of emergence and development, and no less important are the problems and controversies of majaz in the interpretation of the Quran which will be discussed in this paper. This research ia an analytical descriptive study. The conclusion of this study is the majaz approach in interpretation of the Qur’an is worthy of attention given because the many divions of majaz and the relationship between the true meaning (the meaning of haqiqi) and the untrue meaning (the meaning of majazi).